If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3x + 8) = 266 Reorder the terms: 7(8 + 3x) = 266 (8 * 7 + 3x * 7) = 266 (56 + 21x) = 266 Solving 56 + 21x = 266 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + 21x = 266 + -56 Combine like terms: 56 + -56 = 0 0 + 21x = 266 + -56 21x = 266 + -56 Combine like terms: 266 + -56 = 210 21x = 210 Divide each side by '21'. x = 10 Simplifying x = 10
| 5(-2x-7)=-65 | | 5(3-2x)=-95 | | 7(4x+1)=63 | | -2x+20=-4x+20 | | 7(4x+1)=36 | | 10x-6x=2x-6 | | -2x+20=-0.5x+20 | | -2x+20=-2x+20 | | -2x+20=-2x+40 | | -2x+20=-1x+10 | | -2x+20=-20x+200 | | -2x+20=-4+40 | | -2x+20=6x+40 | | -2x+20=4x+40 | | -2x+20=2x+40 | | 0.8-0.4=-6+w | | x^6+x^4-13x^3-13x^2+36x+36=0 | | 6y^2=-47y | | 9x-9=4x+11 | | 12x^9y^10= | | 85=0.12x+77.98 | | Z^2+25=0 | | 3[4-(6y-5)]= | | 3x+3x+3x= | | 8-5[4-(6y-5)]= | | 3(-2)-(3+4)(3+4)= | | x/5-9=7 | | x+x+5+x+x+5= | | y(y+2)(7y-1)=0 | | 7x^3-12x^2+212x=0 | | (8x+3)=(7x+12) | | -2*-2*4= |